Representations of Civil War Violence in Liam O’Flaherty’s "The Sniper" and Saah Millimono’s "Boy, Interrupted": A Comparative Study - Shilan Abdulrahman Abdulkarim (مجلة الباحث, 2026)
This study conducts a comparative literary analysis of Liam O'Flaherty's short tale "The Sniper" (1923) and Saah Millimono's novel “Boy, Interrupted” (2015), exploring their unique yet complimentary representations of civil war. O'Flaherty's piece, which emerged out of the Irish Civil War, is a short, symbolic look at how individuals fight, emphasizing on the psychological damage done to one soldier and the tragic irony of killing your brother. Millimono's novel, an extensive account of the Liberian Civil War, offers a vivid and immersive portrayal of modern "total war," especially with the systemic mistreatment of women and children